PENGUASAAN UNSUR-UNSUR KALIMAT DALAM ILMU NAHWU DENGAN PERMAINAN TEKA-TEKI SILANG - Fikri Abdul Salam; Adhi Setiyawan (Al-Fakkaar, 2023)
The Arabic language is a language with specific rules and sentence elements to be learned. Many students are interested in improving their Arabic language skills but face challenges in using the elements of its sentence structure, making the usage and placement of sentences imperfect. Learning the Arabic language has countless benefits. By understanding Arabic, we can delve deeper into the meaning of the Qur'an, open doors of communication with over 420 million Arabic speakers worldwide, and immerse ourselves in the richness of Arab culture, literature, and history. Therefore, this paper will offer a way to teach students to memorize and use sentences properly and effectively to enhance their understanding of the elements of Arabic sentences, or Nahwu. This will be achieved through creating a game called "Teka-Teki Silang (TTS) Ilmu Nahwu" (Nahwu Crossword Puzzle). Using this game as a teaching medium will facilitate and make learning enjoyable, as its characteristics are easy and flexible. Students will be able to memorize the elements of Arabic sentence structure, achieve the learning objectives, and produce an engaging learning media that motivates them to learn while having fun.